A finite element analysis of two novel screw designs for scaphoid waist fractures. Issue 2 (February 2016) - Varga, Peter; Zysset, Philippe K.; Schefzig, Philip; Unger, Ewald; Mayr, Winfried; Erhart, Jochen
Highlights: We model the osteotomized and fixed scaphoid using the finite element method. The inter-fragmentary motion (IFM) is predicted in three wrist positions. IFM is predominantly rotational in single screw fixation without compression force. Novel screw designs more efficiently restrict IFM compared to simple screws when the interfragmentary compression is below 15–20 N. Wrist position is highly influential, the new screw designs provide no benefit in total flexion. Abstract: The scaphoid is the most often fractured carpal bone. Scaphoid fracture repair with a headless compression screw allows for early functional recovery. The rotational stability of a single screw may be limited, having a potential negative impact on the healing process. Two novel screws have been designed to provide improved rotational stability compared to the existing ones. Using a computational finite element model of a scaphoid osteotomy, we compared the efficacy of one simple screw and the two new screws in restricting inter-fragmentary motion (IFM) in three functional positions of the wrist and as a function of inter-fragmentary compression force. The in-plane IFM was primary rotational and was better restricted by the new screws compared to the conventional one when the inter-fragmentary compression force was below 15–20 N, but provided no clear benefit in total flexion independently of the compression force. To better understand the differences in the non-compressed case, we analyzed the acting moments and investigated the effects of the bending and torsional screw stiffness on IFM. By efficiently restricting the inter-fragmentary shear, the new screws may be clinically advantageous when the inter-fragmentary compression force is partially or completely lost and may provide further benefits toward earlier and better healing of transverse waist fractures of the scaphoid.